Impact of prepubertal exposure to dietary protocatechuic acid on thè hypothalamic-pituitary-testicular axis in rats (2018)
Protocatechuic acid (PCA; 3, 4-dihydroxybenzoic acid) is a phenolic compound widely found in many edible fruits, vegetables, grape wine and plant-derived beverages. The present study investigated the impact of PCA on the hypothalamic-pituitary-testicular axis of rats orally treated with PCA during the period of prepubertal de- velopment to adulthood. Protocatechuic acid was administered to prepubertal male rats at doses of 0, 5, 10, 50 and 100mg/kg body for 45 consecutive days. The results revealed no treatment-related changes in the body weight gain and organo-somatic indices of the hypothalamus, testes, epididymis, prostate gland and seminal vesicle in rats administered with PCA when compared with control. However, prepubertal exposure to PCA significantly enhanced antioxidant enzyme activities and glutathione level whereas it markedly decreased bio- markers of inflammation and oxidative stress in the hypothalamus, testes and epididymis of the treated rats. Protocatechuic acid significantly increased circulatory concentrations of luteinizing hormone and follicle-sti- mulating hormone with concomitant increase in serum and intra-testicular testosterone levels. Moreover, PCA- treated rats exhibited significant increase in marker enzymes of testicular function namely acid phosphatase, alkaline phosphatase, lactate dehydrogenase and glucose-6-phosphate dehydrogenase without statistically sig- nificant increase in spermatogenesis and sperm functional characteristics including sperm count, motility and viability. Light microscopic examination of the hypothalamus, testes and epididymis of rats treated with PCA showed histo-architectures similar to control. In conclusion, prepubertal exposure to PCA is safe and positively impacted reproductive function at sexual maturity in male rats. The observed beneficial effects of PCA is related to its anti-inflammatory and redox regulatory mechanisms.